Clinical InvestigationsSurgery combined with brachytherapy in patients with retroperitoneal sarcomas - Dziewirski, Wirginiusz; Rutkowski, Piotr; Nowecki, Zbigniew I.; Morysiński, Tadeusz; Sałamacha, Maciej; Kulik, Anna; Kawczyńska, Maria; Kasprowicz, Anetta; Łyczek, Jarosław; Ruka, Włodzimierz (Journal of Contemporary Brachytherapy, 2010)
Purpose: The primary aim of this work was to analyze feasibility of combined treatment of retroperitoneal sarcomas (RS): surgery (S) and intraoperative brachytherapy (IOBRT). The secondary aim was to analyze results and complications after this treatment. Material and methods: 84 patients with retroperitoneal sarcomas were qualified for combined treatment (S and IOBRT) between June 1998 and September 2006. 65 of the patients (77.4%) had local recurrences. Sarcomas with intermediate and high grade of histological malignancy (G2, G3 – 76.2%) were the most frequent within the all surgically treated patients. Resection ability (R0/R1) in analyzed group of patients was estimated as 85% (74 cases). After intraoperative evaluation, 57 (67.8%) patients were qualified for IOBRT. Since 2000, in 34 patients (60%) an adjuvant postoperative external beam radiation therapy (EBRT) in dose of 50 Gy was applied. Median follow-up of the surviving patients was 40 months. Results: On the basis of the univariate analysis, relevant aspects negatively influencing overall survival rate within the RS group treated with IOBRT were as follows: surgery of sarcoma recurrence (p = 0.002), higher grade of histological malignancy (p = 0.05), histological type different than liposarcoma (p = 0.05) as well as no adjuvant EBRT (p = 0.05). On the basis of multivariate analysis one can ascertain that relevant factors negatively influencing LRFS in RS patients treated with IOBRT were: surgery due to recurrence of sarcoma (p = 0.008) and lack of EBRT (p = 0.01). Conclusions: Combined treatment (surgery and brachytherapy) was possible to be carried out on 68% of RS patients. The overall number of complications was quite high, however acceptable, taking into consideration the application of extensive, multi-organ treatments in case of sarcoma recurrences in this localization. The results suggest that the method of treatment will improve the final outcome when most of patients will be qualified for treatment of primary sarcomas in experienced centre.